Fungsi Produksi dan Dampak Ekonomi Industri Perkapalan Beserta Jasa Perbaikannya - Suryadi, Suryadi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
This study aimed to determine the effect of input variables on the production of the shipping industry and its service improvement. Input variables to be tested, namely labor, raw materials and capital. To determine the economic impact of the shipping industry and its service improvement, is used the inverse matrix in updating the Input-Output Tables of 2010. The research results revealed that wage labor (Xl) has a positive and significant impact on the shipping industry output value and repair services to the value of coefficient of 0.536. Feedstock production factor (X2) making a positive impact on the shipping industry output and services improvement, amounting to 0.490. Production factor of capital (X3) does not significantly influence industrial production and ship repair services. The scale of the shipping industry and the results of operations improvement services show increasing returns to scale for all three variables when added together, will result in the value of 1.086. Increasing growth of the shipping industry and improvement services, able to spur other economic sectors to grow through multiplier is created. In the event of an increase in demand in the shipping industry and repair services for one unit, the economic sectors affected most of it coming in the shipping industry and repair services for 1.744 unit; Other electrical equipment industry by 0.077 unit; industrial machinery and equipment amounted to 0.056 units; electricity sector amounted to 0.049 unit; goods industries of iron and steel amounted to 0.042 unit and industrial goods of oil refinery by 0.037 unit.Keywords: Increasing return to scale, multiplier, input and output Penelitian ini bertujuan untuk mengetahui pengaruh variabel input terhadap produksi industri perkapalan beserta jasa perbaikannya. V ariabel input yang akan diuji yaitu upah tenaga ketja, bahan baku dan modal. Untuk mengetahui dampak ekonomi industri perkapalan beserta jasa perbaikannya, digunakan matriks invers dalam Tabel InputOutput updating tahun 2010. Dari hasil penelitian diketahui bahwa upah tenaga ketja (Xl) mempunyai pengaruh yang positif dan signifikan terhadap nilai output industri perkapalan dan jasa perbaikannya dengan nilai koefisien sebesar 0,536. Faktor produksi bahan baku (X2) memberikan pengaruh yang positif terhadap output industri perkapalan dan jasa perbaikannya, yaitu sebesar 0,490. Sedang faktor produksi modal (X3) tidak berpengaruh signifikan terhadap produksi industri kapal dan jasa perbaikannya. Skala hasil usaha industri perkapalan dan jasa perbaikannya menunjukkan increasing return to scale karena bila dijumlahkan ketiga variabel bebas, akan menghasilkan nilai 1,086. Peningkatan pertumbuhan industri perkapalan dan jasa perbaikannya, mampu memacu sektor-sektor ekonomi lainnya untuk berkembang lewat multipler (pengganda) yang diciptakannya. Apabila terjadi peningkatan permintaan pada industri perkapalan dan jasa perbaikannya sebesar satu satuan, maka sektor-sektor ekonomi yang terkena dampak paling besar terjadi pada industri perkapalan dan jasa perbaikannya sebesar 1,744 satuan; sektor industri perlengkapan listrik lainnya sebesar 0,077 satuan; sektor industri mesin dan perlengkapannya sebesar 0,056 satuan; sektor ketenagalistrikan sebesar 0,049 satuan; sektor industri barang-barang dari besi dan baja sebesar 0,042 satuan serta sektor industri barang-barang hasil kilang minyak sebesar 0,037 satuan. Kata Kunci : skala hasil yang semakin meningkat, pengganda, masukan dan keluaran